A Novel Spectral Index for Identifying Ferronickel (Fe–Ni) Laterites from Sentinel 2 Satellite Data - Anifadi, A; Sykioti, O.; Koutroumbas, K; Vassilakis, E (Natural Resources Research, 2022)
Field geological mapping is the initial step of preliminary research in mining. However, in the last decades, the rapid progress of remote sensing data processing and its use for reconnaissance of geological outcrops for the purpose of locating possible mining sites gained increasing attention due to the significant time and cost savings. In this study, a new methodology, focused on mapping ferronickel (Fe–Ni) laterite deposits by using Sentinel-2 satellite data, is introduced. It describes a novel spectral index (called laterite spectral index (LSI)) that enhances laterite surface outcrops. To the best of our knowledge, LSI is the first spectral index tailored for this task, concerning minerals that are simultaneously rich in Fe and Ni. The LSI was applied on a continuum removed image by taking advantage of the spectral features present in two specific spectral areas of 490–560 nm and 842–945 nm. The entire methodology was tested and validated on four different excavation sites in eastern Central Greece based on known drillholes. In all excavation sites, the proposed LSI compared favorably with other relative spectral indices proposed in the literature for the detection of Fe-bearing minerals or Fe-oxides.